(untitled) (Latakia University Journal -Medical Sciences Series, 2022)
This study aims to evaluate the fracture resistance and failure patterns of individual polyether ketone ketone (PEKK ) posts and cores restoring indodontically treated premolars. 20 mandibular first premolars ex-tracted for orthodontic reasons were cut above the cementoenamel junction by 2mm. En-dodontic treatment was performed, then samples randomly distributed to two groups, Group 1: Restored with individual milled polyether ketone ketone posts and cores. Group 2: Restored with prefabricated fiberglass -reinforced resin posts and composite cores buildups. The samples were subjected to shear forces at an angle of 45 until the failure oc-curred. The values were recorded in Newton, and the patterns of failure were examined. Statistical analyses were performed using SPSS software (Version 20). The T student test was used for independent groups and the x2 test at a significance level (a=0.05) Results: T-student test showed no statistically significant differences between the means of fracture resistance in the two groups (P= 0.738> 0.05). The mean fracture resistance in group (1) was (423.2 ± 113.28) Newton, while in the group (2) (439.5 ± 100.616) Newton. For failure patterns, the X2 test showed no difference between the two groups (P=0.371>0.05). Conclusion: Within the limitations of this study, individual polyether ketone posts can be used in restoring endodontically compromised premolars.